1989
DOI: 10.1101/gad.3.7.1019
|View full text |Cite
|
Sign up to set email alerts
|

Definition of an efficient synthetic poly(A) site.

Abstract: We constructed and analyzed a synthetic poly(A) (SPA) site that was based on the highly efficient poly(A) signal of the rabbit I~-globin gene. By use of the SPA, we demonstrate that the minimum sequences required for efficient polyadenylation are the AATAAA sequence and a GT/T-rich sequence with the correct spacing of 22-23 nucleotides between them. When placed downstream of the poly(A) site of the human a2-globin gene, the SPA is used exclusively. We predict that the SPA, with its more extensive GT/T-rich seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
260
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(273 citation statements)
references
References 21 publications
13
260
0
Order By: Relevance
“…In plants, the analysis of the pea ribulose-r5-biphosphate carboxylase small-subunit gene suggested the involvement of several upstream and downstream elements (Hunt and MacDonald 1989). In vertebrate systems, it has been shown that an AATAAA and a downstream element are the only necessary requirements for efficient processing and that the polyadenylation site is usually at an A residue (Kessler et al 1986;Levitt et al 1989). However, upstream elements in addition to the downstream element have been described for the SV40 late poly (A) signal (Carswell and Alwine 1989), for the adenovirus late transcription unit (DeZasso and Imperiale 1989), and for the hepatitis B virus (Russnak and Ganem 1990).…”
Section: Discussionmentioning
confidence: 99%
“…In plants, the analysis of the pea ribulose-r5-biphosphate carboxylase small-subunit gene suggested the involvement of several upstream and downstream elements (Hunt and MacDonald 1989). In vertebrate systems, it has been shown that an AATAAA and a downstream element are the only necessary requirements for efficient processing and that the polyadenylation site is usually at an A residue (Kessler et al 1986;Levitt et al 1989). However, upstream elements in addition to the downstream element have been described for the SV40 late poly (A) signal (Carswell and Alwine 1989), for the adenovirus late transcription unit (DeZasso and Imperiale 1989), and for the hepatitis B virus (Russnak and Ganem 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this is achieved by the dominant role of the 59SS and its recognition by U1snRNP, which act to block adjacent PAS recognition. Again, this phenomenon was first described in gene-specific studies (Levitt et al 1989;Zhao et al 1999) but has now achieved genome-wide status (Kaida et al 2010). Early examples of such regulation were found in mammalian viruses, which often need to maximize their gene expression output by selective use of PAS.…”
Section: Alternative Pas (Apa) Define Different Mrna 39 Utrsmentioning
confidence: 99%
“…Poly(A) signals range from 600 to Ͼ1,000 bp. However, previous studies have shown that the required consensus sequence, AATAAAX 22 GT x ͞T x , in a 49-bp sequence produces protein expression equivalent to that of a full-length poly(A) signal in HeLa cells (26). We compared this 49-bp SPA with the 624-bp hGH poly(A) signal present in pCMV5-␤-gal.…”
Section: Evaluation Of the Length Of An Ivsmentioning
confidence: 99%